ACL reconstruction with lateral plasty reduces translational and rotatory laxity compared to anatomical single bundle and non-anatomical double bundle surgery: An in vivo kinematic evaluation with navigation system. (October 2019) - Grassi, Alberto; Signorelli, Cecilia; Lucidi, Gian Andrea; Raggi, Federico; Macchiarola, Luca; Roberti Di Sarsina, Tommaso; Muccioli, Giulio Maria Marcheggiani; Filardo, Giuseppe; Zaffagnini, Stefano
Abstract: Background: Significantly better stability may be achieved with a Single Bundle Lateral Plasty (SBLP) reconstruction compared with the Single Bundle (SB) and Double Bundle (DB) procedures. Methods: The study included 42 patients who underwent ACL reconstruction. Patients were randomly selected for one of the following surgical procedure defining three study groups: Single-Bundle-Lateral-Plasty, Single-Bundle and Double-Bundle procedures. Laxity evaluation was performed with an intraoperative navigation system. Lachman test (AP30), Drawer test (AP90), Varus-Valgus stress test at 0° and 30° knee flexion (VV0, VV30), Internal-External rotation (IE30, IE90), and pivot shift (PS) test are the clinical test executed for the laxity evaluation. Laxity reduction was defined as the difference between laxity before the fixation of the graft used for the reconstruction and the laxity just after its fixation. Findings: For all the analyzed surgical techniques, the pre-reconstruction laxity values were statistically higher ( P  < 0.05) than the post-reconstruction values for all the analyzed tests. The analysis of the Drawer test and Internal-External rotation at 30° and 90° of knee flexion, highlighted a significant difference at time zero after surgery among the three study groups. The results showed that the SBLP technique had the highest reduction values compared to SB (PIE90  = 0.001) and DB (PAP90  = 0.012; PIE30  = 0.021; PIE90  = 0.003) techniques. Interpretation: SBLP technique showed significantly superior results in terms of antero-posterior and internal-external laxity reduction at time-zero after ACL reconstruction. Highlights: Contrasting findings in short- and long- term results have not identified which surgical procedure is superior to the others SBLP is more effective in controlling AP translation at 90°, and IE tibial rotation at 30° and 90° than the other techniques. No differences were found regard to varus-valgus rotation and pivot shift test among the different ACL reconstruction approaches.